Pengaruh Profitabilitas, Ukuran Perusahaan dan Independensi Komite Audit Terhadap Audit Delay - Salsa Aulia Putri; Indupurnahayu Indupurnahayu; Desmy Riani (Komunitas Dosen Indonesia, 2024)
There is a common occurrence of financial report filing delays among firms listed on the Indonesia Stock Exchange, particularly in the banking sector. Findings from this study highlight the significance of prepared reports in a timely manner. It is imperative that businesses and auditors collaborate to finalize and submit financial reports to the Indonesia Stock Exchange (IDX) well in advance of the scheduled date to mitigate the effects of delays. The goal of this research is to find out between 2020 and 2022 whether Indonesian banking businesses that are listed on the stock market had audit delays and how audit committee independence, company size, and profitability interact with each other. Utilising secondary data collected over the course of three years from 41 different banking organisations, this research employs a quantitative descriptive methodology. Our research shows that audit delay is affected by profitability, firm size, and the independence of the audit committee all at once. A positive correlation between audit committee independence and audit delay exists, although profitability and firm size both exhibit negative correlations with audit delay. Given that management is more likely to disclose financial results promptly to communicate good news, this suggests that larger, more profitable organisations have shorter audit delays. Conversely, greater audit committee independence leads to longer audit delay as greater oversight requires more time to produce high quality financial statements.